Advances in Space Research - Advances in Space Research (Elsevier, 2026)
The COSPAR publication Advances in Space Research (ASR) is an open journal covering all areas of space research including: space studies of the Earth's surface, meteorology, climate, the Earth-Moon system, planets and small bodies of the solar system, upper atmospheres, ionospheres and magnetospheres of the Earth and planets including reference atmospheres, space plasmas in the solar system, astrophysics from space, materials sciences in space, fundamental physics in space, space debris, space weather, Earth observations of space phenomena, etc.
FI 0.76
Q2
Keywords: Earth; Space & Environmental Sciences; Aeronautics - Space Flight; Ciencias de la tierra; Aeronáutica; Vuelo espacial; Acuerdos transformativos; Transformative agreements; Meteorología; Clima